2017
DOI: 10.5539/jel.v6n2p305
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Maternal Acceptance-Rejection Levels and Preschoolers’ Social Competence and Emotion Regulation Skills

Abstract: The purpose of this research was to examine the relationship between maternal acceptance-rejection levels and preschool children's social competence and emotion regulation skills. The study group of the research, which was designed in survey method, consisted of 303 voluntary mother-child dyad. The participant children were attending a preschool in 2014-2015 academic year, in Istanbul and they were selected by random cluster sampling method. The "Personal Information Form", the "Parental Acceptance-Rejection Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
3
0
1
Order By: Relevance
“…Thompson, Lewis and Calkins (2008) found that as children grow up, they can manage their self-control processes more effectively, contributing to gradual improvement of emotion regulation. This result agrees with the research finding reported by Bayındır, Güven, Sezer, Akşin Yavuz and Yılmaz (2017), showing that 6-year-old children's emotion regulation skills are better than those of 5year-old children, that is, children's emotion regulation skills get better as they grow up.…”
Section: Discussionsupporting
confidence: 92%
“…Thompson, Lewis and Calkins (2008) found that as children grow up, they can manage their self-control processes more effectively, contributing to gradual improvement of emotion regulation. This result agrees with the research finding reported by Bayındır, Güven, Sezer, Akşin Yavuz and Yılmaz (2017), showing that 6-year-old children's emotion regulation skills are better than those of 5year-old children, that is, children's emotion regulation skills get better as they grow up.…”
Section: Discussionsupporting
confidence: 92%
“…Self-compassion also contributes to social relationships (Umphrey & Sherblom, 2014) and social commitment (Neff & Germer, 2018). Parents' acceptance and warmth toward their children shows a positive relationship with children's social skills (Bayındır et al, 2017). Parents being compassionate, sensitive, and observing the child shows a relationship with children's healthy interaction with their peers (Engels et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Social competence is described as a structure formed with social harmony, social performance, and social skills (Bayindir, Guven, Sezer, Aksin-Yavuz & Yilmaz, 2017). Social competence skills include child's appropriate reaction regarding the situation s/he is in, her/his behaviors regarding their peers' rules and behaviors of healthy communication (Aral & Kadan, 2018).…”
Section: Social Competencementioning
confidence: 99%
“…On the other hand, parents' negative communication and non-supportive reactions such as strict parental behavior, punishment or stress in parents affect their communication with their children negatively. Studies examining the effects of mothers on their children's socialization have found a positive relationship between mothers' emotional supportive reactions and their children's social competence skills (Bayindir, Guven, Sezer, Aksin-Yavuz & Yilmaz, 2017;Ozkan & Aksoy, 2017). Various perspectives emphasized that children's social competence skills are based on their relationship with their fathers.…”
Section: Children's Social Competence Levels and Their Parents' Communication With Themmentioning
confidence: 99%